BAḤR AL-MADHĪ AND THE ESTABLISHMENT MOMENTUM OF ḤADĪTH STUDIES IN NUSANTARA IN THE 20TH CENTURY - Hilmy Firdausy; Rifqi Muhammad Fatkhi; Fuad Thohari (Peminat Ilmu Ushuluddin, 2022)
This paper intends to strengthen the view that Islam vernacularizing happened in the sharḥ of ḥadīth that provided new distinctions in the meaning of the Prophet’s Ḥadīths. Baḥr al-Madhī Syarah Bagi Mukhtaṣar Saḥīḥ al-Tirmidhī written by Muhammad Idris al-Marbawi (1896-1989) provided quite copious data on this matter. Instead of obscuring the Prophet’s ḥadīths, the subjectivity, and locality of al-Marbawi as a Nusantara Muslim scholar enriches the contextualization of the meaning of ḥadīth so that the non-Arab communities can understand the ḥadīths well. The abundant textual data in Baḥr al-Madhī also confirmed that the study of Nusantara ḥadīths had been established in the 19th and 20th centuries AD. This paper strengthened Oman Fathurrahman’s thesis which showed that the roots of the Nusantara ḥadīths writing tradition have existed since the 17th century. On the other hand, this paper refuted several academics’ opinions such as Brown (1966) and Azra (1997) who said that the study of ḥadīths was stagnant.